Architecture and belonging: Migration, re-territorialisation and self-identity - Glusac, Tanja (Curtin University, 2015)
This thesis investigates connections between architecture, culture, memory and habitus and the role architecture and the built environment play in promoting self-identity and belonging. It explores these issues through the complexity of migration resettlement and its impact on built forms, demonstrating the rich qualities of life and personal being that individuals bring to architecture and the failure of conventional architectural discourse and practice to acknowledge or respond to the necessity of informing identity and belonging.